2019
DOI: 10.1186/s40468-019-0093-8
|View full text |Cite
|
Sign up to set email alerts
|

‘Remark or retake’? A study of candidate performance in IELTS and perceptions towards test failure

Abstract: It is becoming increasingly important for individuals for whom English is a second language to demonstrate their linguistic credentials for academic, work and employment purposes. One option is to undertake International English Language Testing System (IELTS), which involves attempting to meet the linguistic entrance criteria set by a gatekeeping institution in the skills of listening, reading, writing, and speaking. Yet limited information is available in the public domain concerning the success of test-take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The International English Language Testing System (IELTS) is a standardized English test globally used for assessing English language proficiency of the test takers in various contexts such as education, employment, and immigration (Fernandez, 2018). The IELTS was jointly developed by the British Council, The University of Cambridge Local Examination Syndicate (UCLES) and IDP Education Australia (Pearson, 2019;Quaid, 2018). The IELTS listening test is made up of 40 questions divided into four major sections.…”
Section: Listening Comprehension Testmentioning
confidence: 99%
“…The International English Language Testing System (IELTS) is a standardized English test globally used for assessing English language proficiency of the test takers in various contexts such as education, employment, and immigration (Fernandez, 2018). The IELTS was jointly developed by the British Council, The University of Cambridge Local Examination Syndicate (UCLES) and IDP Education Australia (Pearson, 2019;Quaid, 2018). The IELTS listening test is made up of 40 questions divided into four major sections.…”
Section: Listening Comprehension Testmentioning
confidence: 99%
“…It was evident Min Jung and Yuri’s feelings of frustration and disappointment also stemmed from lower-than-expected written performance. IELTS test-takers’ assumption of linear gains across multiple test undertakings and confusion with inconsistent scores is documented in the literature (Hamid, 2016; Pearson, 2019). It may have been accentuated in the present study since the learners had recruited outside expertise to supplement existing preparation activities and implicitly expected progression over the project.…”
Section: Resultsmentioning
confidence: 99%
“…Prior research has shown the practice of undertaking rehearsal tasks in simulated test conditions is a central feature of self-directed and teacher-led IELTS Writing preparation (Allen, 2016; Chappell et al, 2019; Hu & Trenkic, 2019; Mickan & Motteram, 2009; Smirnova, 2017). Rehearsal essays are popular with candidates because they provide opportunities to self-evaluate test format familiarity (Pearson, 2019), enhance understanding of typical topics and prompt frames (Coffin, 2004; Craven, 2012), and practice skills and strategies used to lower the burden of test taking (Chappell et al, 2019; Winke & Lim, 2014). Nevertheless, improving future test performance via rehearsal essay writing is not assured.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study employed the International English Language Testing System (IELT S), a standardized and globally accepted English test widely used for assessing English language proficiency of the test takers in a great variety of contexts such as education, employment, and immigration as an instrument for the measurement of participants' English listening proficiency. The IELTS was jointly developed by the British Council, The University of Cambridge Local Examination Syndicate (UCLES), and IDP Education Australia (Pearson, 2019;Quaid, 2018). There were four parts in the IELTS listening test: parts 1 and 2 included a conversation and a prompted monologue with transactional purposes and parts 3 and 4 consisted of a discussion dialogue and a monologue in academic contexts (Alavi et al, 2018;Phakiti, 2016).…”
Section: The Ielts Listening Testmentioning
confidence: 99%